Modeling risks in real estate development projects: a case for Egypt - Marzouk, Mohamed; Aboushady, Ahmed (International Journal of Strategic Property Management, 2018)
Risk analysis is a vital step in the succession of construction projects. However, no adequate researches have been conducted to assess, and quantify risk events in real estate projects in developing countries, and particularly in Egypt.This research recommends Fuzzy Quantitative Risk Assessment Model to quantify risk factors participated in real estate development projects. Model is composed of two components: 1) Fuzzy Fault Tree (FT) that determines root causes of each risk, probability of its occurrence, and probability of mitigation strategies failure; and 2) Fuzzy Event Tree (ET) that calculates crisp value of Expected Monetary Value (EMV) of allowance of mitigation of the identified risks. Causes of risk are determined through literature review and interviews with experts in field. Risk probability occurrence is determined using five linguistic terms, defined either triangular or trapezoidal membership functions which are developed using modified horizontal approach and an interpolation technique. Two-step Delphi technique is used to achieve consensus on the root causes and logical representation of the Fault Tree. Fuzzy importance analysis is performed to rank different root causes for identified risks according to their criticality to probability of occurrence. A Case Study is presented to evaluate results obtained from model, in terms of Expected Monetary Value (EMV), and fuzzy probability of failure for each risk participated in case study.